Safely advancing a spacefaring humanity with artificial intelligence - Richards, Catherine E.; Cernev, Tom; Tzachor, Asaf; Zilgalvis, Gustavs; Kaleagasi, Bartu (Frontiers in Space Technologies, 2023)
A ‘Space Renaissance’ is underway. As our efforts to understand, utilize and settle space rapidly take new form, three distinct human-space interfaces are emerging, defined here as the ‘Earth-for-space’, ‘space-for-Earth’ and ‘space-for-space’ economies. Each engenders unprecedented opportunities, and artificial intelligence (AI) will play an essential role in facilitating innovative, accurate and responsive endeavors given the hostile, expansive and uncertain nature of extraterrestrial environments. However, the proliferation of, and reliance on, AI in this context is poised to aggravate existing threats and give rise to new risks, which are largely underappreciated, especially given the potential for great power competition and arms-race-type dynamics. Here, we examine possible beneficial applications of AI through the systematic prism of the three economies, including advancing the astronomical sciences, resource efficiency, technological innovation, telecommunications, Earth observation, planetary defense, mission strategy, human life support systems and artificial astronauts. Then we consider unintended and malicious risks arising from AI in space, which could have catastrophic consequences for life on Earth, space stations and space settlements. As a response to mitigate these risks, we call for urgent expansion of existing ‘responsible use of AI in space’ frameworks to address ‘ethical limits’ in both civilian and non-civilian space economy ventures, alongside national, bilateral and international cooperation to enforce mechanisms for robust, explainable, secure, accountable, fair and societally beneficial AI in space.